2018
DOI: 10.2340/16501977-2340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of therapeutic exercise on knee osteoarthritis after intra-articular injection of botulinum toxin type A, hyaluronate or saline: A randomized controlled trial

Abstract: Therapeutic exercise plus botulinum toxin type A or hyaluronate injection can significantly reduce pain and improve knee functioning. Botulinum toxin type A plus therapeutic exercise appears to be more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…Meanwhile, it was suggested that botulinum toxin type A plus therapeutic exercise seems to get better results. 122…”
Section: Other Therapiesmentioning
confidence: 99%
“…Meanwhile, it was suggested that botulinum toxin type A plus therapeutic exercise seems to get better results. 122…”
Section: Other Therapiesmentioning
confidence: 99%
“…The analysis found that BoNT-A IA injection had a greater improvement than placebo in terms of the VAS pain scale and WOMAC questionnaire score in both the short-term and long-term treatment periods. Additionally, in the studies of Bao et al 16 and Mendes et al, 17 BoNT-A IA injection demonstrated an acceptable safety profile, with improvements in the Physical Component Summary-36, Mental Component Summary-36, and ultrasound measurement of synovial hypertrophy.…”
Section: Discussionmentioning
confidence: 92%
“…Among the remaining 19 studies, 14 studies were excluded for lack of useful data. Finally, 5 RCTs [13][14][15][16][17] were used to evaluate the efficacy and safety of BoNT-A in painful knee OA ( Figure 1 describes the search process in detail). Table 1 shows the baseline characteristics of these 5 studies.…”
Section: Characteristics Of Individual Studiesmentioning
confidence: 99%
“…After the screening selection through titles, abstracts, and full texts, 38 articles were screened for eligibility. Finally, six articles met the inclusion criteria and were included in this systematic review [ 36 , 37 , 38 , 39 , 40 , 41 ] (see Figure 1 ; PRISMA flow diagram). Only two studies openly disclosed having no conflict of interest concerning funding [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%